Poor nutritional status affecting blood donor deferral pattern at blood centre of North-East region of India - Maheshwari, Ashish; Kumari, Nawanita; Prakash, Satya (International Journal Of Community Medicine And Public Health, 2020)
Background: Due to the stringent criteria for the selection of blood donors, donor deferral rate is increasing day by day, leading to a decrease in donor base for the blood bank. This study was done to analyze the incidence of deferral rate and deferral pattern to review the donor recruitment and retention policy and to highlight the role of nutrition improvement. Methods: A retrospective observational single-centre study was conducted in the department of transfusion medicine of North-East region of India from April 2018 to April 2019. Results: During the study period, a total of 3920 donations were made, and a total of 1992 donors were deferred. The overall deferral rate was 33.6% with male deferral rate was 29.4%, and the female deferral rate was 78.4%. Low haemoglobin and low weight contribute around 50% of total deferral. Conclusions: Analysis of donor deferral in a specific region is of utmost significance. Strategies to improve the health status of the population will help to increase donor pool in future, making easy availability of blood. The nutritional programme should be initiated for this group of deferred donors.